Anisotropic fracture in nacre-like alumina. (February 2023) - Duminy, Thomas; Henry, Ronan; Adrien, Jérôme; Doitrand, Aurélien; Meille, Sylvain
Abstract: Fracture in nacre-like alumina is studied experimentally and numerically with alumina platelets main alignment direction perpendicular (along-configuration) to the one commonly tested (across-configuration) in the literature. In along-configuration, brittle failure is noted after crack initiation with no macroscopic crack deviation, unlike what is observed in across-configuration. However, NLA exhibits in along configuration initiation critical stress intensity factor K I c = 5.3 ± 0.5 MPa m 1 / 2, in the same order of magnitude as in across-configuration. The increase in K I c compared to monolithic alumina can be explained by a phenomenon of crack initiation containment at the interface between platelets. Unstable crack propagation occurs just after initiation, mainly following the platelet interfaces which results in crenelated fracture surfaces with crack decentering with respect to the initial notch tip. Highlights: Nacre-like alumina in so-called "along-configuration" exhibits a linear-elastic behavior until brittle fracture. Initiation stress intensity factor is 1.5 time higher than monolithic polycrystalline alumina.. The reinforcement is explained by a phenomenon of crack initiation containment induced by the microstructure. The crack containment happens at the interface between one to few adjacent alumina platelets.